Applying fuzzy MCDM for financial performance evaluation of Iranian companies - Ghadikolaei, Abdolhamid Safaei; Esbouei, Saber Khalili; Antucheviciene, Jurgita (Technological and Economic Development of Economy, 2014)
Financial performance evaluation is very important in a highly competitive business environment. Accordingly, an accurate and appropriate performance evaluation is critical. Financial performance indicators reflect the competitiveness of a company and they must be carefully identified in the evaluation process. Generally, accounting measures are used for performance evaluation. However, these measures are not sufficient for performance evaluation in the today’s competitive economy. Therefore, value based measures have recently been introduced to express the company value. In this study, a hybrid approach is proposed for financial performance evaluation of automotive companies of Tehran stock exchange (TSE). For this purpose, a hierarchical financial performance evaluation model is structured based on the accounting measures and economic value measures. In this approach Fuzzy Analytic Hierarchy Process (FAHP) is applied to determine weights of criteria. Then the companies are ranked by using Fuzzy VIKOR (VlseKriterijumska Optimizacija I Kompromisno Resenje (in Serbian), Fuzzy Additive Ratio Assessment (ARAS-F) and Fuzzy Complex Proportional Assessment (Fuzzy COPRAS), simultaneously. Also results of three outranking methods are combined by using the mean ranks. The results represented the highest importance of economic value measures than accounting measures in financial performance evaluation of companies. Six companies were ranked applying the proposed approach.